2010
DOI: 10.1016/j.jviscsurg.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and urinary dysfunction after proctectomy for rectal cancer

Abstract: Sexual and urinary dysfunction occur frequently after rectal surgery. Total mesorectal excision (TME) is currently the optimal technique for resection of rectal cancer, providing superior carcinological and functional outcomes. Age, pre-operative radiation therapy, abdominoperineal resection, and surgery which fails to respect the "sacred planes" of TME are the four major risk factors for post-operative sexual and urinary sequelae. In the era of TME, postoperative sexual dysfunction ranges from 10-35%, dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 60 publications
1
63
1
2
Order By: Relevance
“…Rehabilitation programs for these patients are complex. Psychological evaluation and support of the patient and his or her partner are mandatory, resulting in enhancing the response to pharmacologic therapy (Eveno, Lamblin, Mariette, & Pocard, 2010). Among the medications available, the efficacy of sildenafil was demonstrated in a study where 32 patients were randomized to medical treatment or placebo after rectal resection (Lindsey et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation programs for these patients are complex. Psychological evaluation and support of the patient and his or her partner are mandatory, resulting in enhancing the response to pharmacologic therapy (Eveno, Lamblin, Mariette, & Pocard, 2010). Among the medications available, the efficacy of sildenafil was demonstrated in a study where 32 patients were randomized to medical treatment or placebo after rectal resection (Lindsey et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Duran et al 20 noted a 17.8% decrease in the sexual function of men compared with the preoperational period after abdominoperineal resection and low anterior resection. Both erection and ejaculation were impaired significantly.…”
Section: Pelvic Surgerymentioning
confidence: 99%
“…However, surgeons have direct attention to the preservation of the pelvic nerves in the surgical treatment of rectal cancer. Some authors have investigated the mechanisms of neural injury aiming to promote the preservation of the autonomic innervation of the pelvis and to thus reduce the incidence of functional sequelae (6,7,19,22,26,32) . Such mechanisms include the injury of either the inferior hypogastric plexus or the pelvic splanchnic nerves due to violation of the avascular plane between the visceral and parietal pelvic fascia (22,27) .…”
Section: Discussionmentioning
confidence: 99%
“…Such mechanisms include the injury of either the inferior hypogastric plexus or the pelvic splanchnic nerves due to violation of the avascular plane between the visceral and parietal pelvic fascia (22,27) . Ligation of the inferior mesenteric artery at its origin, close to the aorta, with sectioning of superior hypogastric plexus fibres concomitant or not to sectioning of the inferior hypogastric plexus is another neural injury mechanism that has been investigated (6,7,19,22,27,32) . Studies based on cadaveric surgery showed that dissection along the presacral fascia and injury of the levator ani nerve, which innervates the levator ani muscle, a crucial component of the urinary and faecal continence system, are also causes of sequelae affecting the pelvic floor (32) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation